HUBUNGAN ANTARA DISIPLIN KERJA DAN MOTIVASI KERJA DENGAN PRODUKTIVITAS KERJA DOSEN DI LINGKUNGAN UNIVERSITAS ISLAM â€œ45â€ BEKASI - Lubis, Rabiyannur (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2012)
The purpose of this study was to determine the relationship between the discipline of work and Motivation of work in lecturer work productivity at UNISMA-Bekasi. By using the survey method, the study sample was employees at UNISMA-Bekasi. Conclusions of this study are: First, there is a positive relationship between lecturer?s discipline of work and motivation of work that showed that if the effectiveness of improved work discipline, then the lecturers work productivity will increase. Second, there is a positive relationship between work motivation and productivity of work that shows that if the lecturer work motivation improved, then the employees will increase productivity. Third, there is a positive relationship between the discipline of work and motivation working together with the lecturer work productivity. This suggests that if the effectiveness, work discipline and motivation working together to be improved, then the lecturers work productivity will increase.